AN EXPLORATORY, OBSERVATIONAL CLINICAL STUDY TO EVALUATE THE EFFECTIVENESS OF BLOODLETTING BY ALFASDH IN ARABIC AND MODERN MEDICINE - Ahmed Ahmed A. Rawwash; Emad Ahmed Hussein; Mahmoud Farok Moghazy; Wafaa Akl; Ebtisam Hashem Zaher (International Journal of Islamic and Complementary Medicine, 2026)
This study aimed to explore the effectiveness of the Alfasdh (BA) method in the treatment of various diseases through an observational clinical study. The study was conducted from April 2023–April 2024 on 35 outpatients divided into neurological (n=18) and surgical (n=17) groups, with evaluation of quality of life (EQ-5D-Y-5L) and pain (VAS) before, during, and after therapy. The results showed no significant difference in quality of life between groups, as well as no significant difference in pain during therapy, but there was a significant difference after therapy, indicating greater improvement in the neurological group. Overall, BA has the potential to provide clinical benefits, especially in neurological cases, although further research with a larger sample size and longer follow-up is needed to confirm its long-term effectiveness.